The Global HIV Epidemics among Men Who Have Sex with Men - Beyrer, Chris; Wirtz, Andrea L.; Walker, Damian; Johns, Benjamin; Sifakis, Frangiscos; Baral, Stefan D. (World Bank, 2012)
Men who have sex with Men (MSM) are currently at marked risk for HIV infection in Low- and Middle-Income Countries (LMICs) in Asia, Africa, Latin America and the Caribbean, and in Eastern Europe and Central Asia. Estimates of HIV prevalence rates have been consistently higher among MSM than for the general population of reproductive-age men virtually wherever MSM have been well studied. Although scarce, HIV incidence data support findings of high acquisition and transmission risks among MSM in multiple contexts, cultural settings, and economic levels. Research among MSM in LMICs has been limited by the criminalization and social stigmatization of these behaviors, the safety considerations for study participants, the hidden nature of these populations, and a lack of targeted funding. Available evidence from these countries suggests that structural risks social, economic, political, or legal factors in addition to individual-level risk factors are likely to play important roles in shaping HIV risks and treatment and care options for these men. Services and resources for populations of MSM remain markedly low in many settings. They have limited coverage and access to HIV/AIDS prevention, treatment, and care services with some estimates suggesting that fewer than one in ten MSM worldwide have access to the most basic package of preventive interventions.